Affordable Health Insurance Options for Small Business and Low-Wage Workers Remains Elusive: Experience With New Health Reimbursement Arrangements in New Jersey - Joel C. Cantor ScD; Jolene Chou MPH; Margaret Koller MS; Katherine Hempstead PhD (SAGE Publishing, 2023)
Low-wage workers and those employed by small businesses are least likely to be offered health insurance coverage and they are over-represented among the uninsured. Two new forms of health reimbursement arrangements (HRAs) that allow employers to help fund individual market coverage for workers have been touted as breakthrough strategies to help fill this gap. Despite several years of experience and low adoption, little is known about employer understanding of or views about these HRA options. Consistent with other evidence, only 11.8% of New Jersey employers we surveyed offer or plan to offer either of the HRA options. Few respondents (18.5%) report familiarity with either option. Even among businesses that offer or plan to offer this form of HRA, under half (47.6%) say that they are familiar with them. Other reasons cited for not offering these options include broker advice and complexity. While more investigation is needed, these findings suggest that new strategies should be explored to fill the gap in health insurance for low-wage and small business employees.